Spectral cathodoluminescence analysis of hymenopteran mandibles with different levels of zinc enrichment in their teeth. Issue 1 (January 2017) - Jorge, Alberto; Polidori, Carlo; Garcia-Guinea, Javier; Nieves-Aldrey, José Luis
Abstract: The inclusion of Zn in insect mandibles affects their hardness and is functional to their use during feeding or reproducing. However, little is known on the chemical/structural base of Zn enrichment. Here, we found that cathodoluminescence (CL) technique revealed two different types of CL spectra in the mandibles of Hymenoptera, depending on the Zn enrichment level assessed by Energy Dispersive X-ray Spectroscopy (EDS). Individuals having negligible traces to low % of Zn in their mandible teeth (≤3 wt%) presented a wide band of luminescence in the visible range which resembled those observed in the CC structures of graphite. This spectrum is probably characteristic for un-enriched cuticle, since it did not differ from those obtained from the Zn-lacking inner part of mandibles. Individuals with moderate to high % of Zn in their mandible teeth (≥7 wt%), instead, presented additional CL peaks in the ultraviolet range. Comparisons with different minerals of Zn suggest that these peaks could be related with OZnO bonds, with hydroxyl groups and with zinc-chlorine links (in agreement with Cl high levels detected by the EDS). Being a non-destructive technique, CL allows large comparative studies of the chemistry of metal-enriched insect cuticle even using unique specimens, such as those deposited in Natural History Museums. Graphical abstract: Highlights: Two types of cathodoluminescence spectra are produced by mandibles of Hymenoptera. This difference is directly linked with the Zn enrichment level of mandible teeth. Only high Zn enrichment level produces spectral peaks in the UV range. Comparisons with Zn minerals suggest how Zn incorporates into cuticle matrix. This non-destructive technique allows comparative studies using unique specimens.